Managerialism - Janet Newman; John Clarke (Universidade Federal do Rio Grande do Sul, 2012)
This article explores the significance of managerialism as a concept for thinking about projects of state reform across the last forty years. Making particular reference to the United Kingdom and its role in the proliferation of the New Public Management, the article suggests that managerialism (as an ideology) and managerialisation (as a process of transformation) combine to produce what we describe as a managerial state. In such a form of state, previous organizational arrangements and systems of power, authority and process based around a combination of bureaucracy and professionalism are reconfigured around managerial authority: theright to manage. Drawing on a conception of the dispersal of power in processes of state reform, we suggest that it is managerialism that gives both ideological and organizational coherence to the complex organizational landscapes that have emerged from state reform projects. Blurred boundaries, hybridized organizational forms, innovative governance arrangements and new apparatuses of accountability and evaluation arearticulated by the promises of greater managerial freedom and authority. The article concludes by speculating on what the turn to austerity in European politics might meanfor managerialism and the dispersal of state power.